Kulturna krajina v teoriji - Juvanec, Borut (Urbani izziv, 2002)
The city grows from the seed to the core. The historical core is the central part with historical significance, around which other programmes are aligned. Possibilities define growth and density of a city, but this is the source of problems. Growth is influenced by activities moving, changes in social and political life, but also important elements of culture and sports. Visibility,sometimes termed beauty, is only the external layer of the interior, the essence itself. A functioning village cannot be ugly. Fire, the fireplace, house, home, village, city (survival, needs and possibilities) are closer to the circle and theory, than can be expected. Growth of architecture from the detail to spatial planning is the fruit of human balancing only in detail. Cities grow according to their own logic. The role of professions is therefore limited only to the establishment of strategies and controlling their growth. Things are much simpler, than we can imagine.
Keywords: architecture; arhitektura; mesta; mestna jedra; teorija arhitekture